The development of an intraorganizational Merchant and Personal Shopper E-Commerce System (MPSAS) / Nor Azila Awang Abu Bakar and Nur Shalina Ismail - Awang Abu Bakar, Nor Azila; Ismail, Nur Shalina (Universiti Teknologi MARA, Perak, 2022)
Personal shopper service currently is seen as a more convenient way to assist buying process. The personal shoppers are often employed by department stores and boutiques, although some are freelance or work exclusively online. For a merchant hiring personal shoppers, managing the transaction without a proper management system may cause the personal shoppers had difficulties in integrating the orders received from their customers. Additionally, communication problems often happened between the merchant and personal shoppers where the response time taken to interact with each other may took several hours thus affecting late response given to the customers. Response time is a critical factor in the service industry. The objectives of this research are; 1) To identify current business process and problems related to personal shopper agent service. 2) To design and develop an intraorganizational e-commerce website for personal shopper agent service. 3) To evaluate the functionality and usability of the developed e-Commerce website. This research has been initiated by preliminary analysis on the system requirement based on literature review and survey. Upon completing requirement gathering, the design phase took place to produce system and database conceptual design for the system. The e-Commerce system named as MPSAS was developed by using MySQL as the back-end database while the front-end was created using programming languages namely HTML, CSS and JavaScript. Lastly, system testing was conducted to test MPSAS functionality and usability. Based on the survey and usability testing, the results indicated that the system is capable to serves its designated functions. Three expert users and thirty potential users were involved in the usability testing. Based on the result, the highest mean gathered is for User Interface Construct which is 4.67 (SD=0.43). As all means are above 4 and standard deviation (SD) are less than 1, this shows that the usability of the system is good and user responses has only small dispersion. This paper provides insight on an application that can help a merchant-based company providing personal shopper services to manage transaction within the organization. Order management and communication between parties in the organization are enhanced by the newly computerized system.